CYTOGENETIC EFFECTS OF TICK-BORNE TRANSMITTED CO- OR MONOINFECTIONS DEPENDING ON THE VARIANTS OF GLUTATHIONE-S-TRANSFERASE GENES (GSTM1 OR GSTT1) IN THE PATIENT’S GENOTYPE - N. N. Ilyinskikh; E. N. Ilyinskikh; E. V. Zamyatina; V. P. Zuevskiy (Журнал инфектологии, 2018)
Aim is to assess repeatedly cytogenetic effects of co- or monoinfection caused by Lyme borreliosis and tick-borne encephalitis during the acute and convalescent periods of the disease depending on variants of glutathione-S-transferase (GSTM1 or GSTT1) genes in the patient’s genotype. Material and methods: The study included 186 patients and 166 healthy (control) residents of the north of the Tomsk and Tyumen regions, who were examined by clinical, laboratory and cytogenetic methods (micronucleus analysis). Among the 186 examined patients, Lyme borreliosis was diagnosed in 65 individuals, tick-borne encephalitis was in 59 patients, and coinfection was found in 62 individuals. The material for the study (smears of buccal cells) was obtained repeatedly during admission of patients to treatment, and also after 1 week, 1, 3 and 6 months. Polymerase chain reaction was used to analyze the alleles of the GSTM1 and GSTT1 genes. Results: significant increase in the frequency of micronucleated buccal cells in patients with coinfection, as compared with the groups of control and patients with monoinfection. The significantly increased frequency of micronucleated cells was associated with the mutant inactive alleles of the GSTM1(0/0) and GSTT1(0/0) genes. If the patients were carriers of the mutant allele of the GSTM1(0/0) gene, the cytogenetic instability could persist for half a year. It was found that chronic arthritis in the Lyme borreliosis patients was associated with a long persistence of an increased frequency of micronucleated cells. Conclusion: Significant differences in the frequency and the lasting of persistence of micronucleated cells between groups of patients with coinfection and monoinfections were found. The most significant increase in those parameters was detected in the coinfected patients in whose genotype contained non-active forms of the GSTM1(0/0) and GSTT1(0/0) genes.